The Influence of the Management of Navigation Aids and Employee Performance on Maritime Safety - St. Syamsidar; A. Nur Insan; Mujahid Yunus (Journal La Sociale, 2026)
Maritime safety is a fundamental element in supporting secure, efficient, and sustainable sea transportation, particularly in strategic maritime regions such as Makassar. This study aims to analyze the effect of SBNP (Sarana Bantu Navigasi Pelayaran) management and employee performance on maritime safety at the District of Navigation Type A Class I Makassar. The research adopts a quantitative approach using survey data collected from 100 respondents, with instruments measured through a Likert scale. Data analysis was conducted using validity tests, reliability tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²). The results of the validity and reliability tests confirm that all research instruments are valid and reliable, indicating strong internal consistency. The partial regression analysis reveals that SBNP management does not have a statistically significant effect on maritime safety, suggesting that the mere availability and procedural management of navigational aids are insufficient to directly enhance safety outcomes. In contrast, employee performance shows a positive and highly significant influence on maritime safety, highlighting the critical role of human resources in ensuring the effective operation, maintenance, and responsiveness of navigational systems. Simultaneously, the F-test results indicate that SBNP management and employee performance together have a significant effect on maritime safety. Furthermore, the coefficient of determination demonstrates that 94.2% of the variation in maritime safety can be explained by the combined influence of SBNP management and employee performance, while the remaining 5.8% is affected by other factors outside the model.